2014
DOI: 10.5223/pghn.2014.17.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Tolerance Assessment of a Lutein-fortified Infant Formula

Abstract: PurposeTo evaluate safety, gastrointestinal tolerance, and growth of a new experimental starter formula (NESF) fortified with lutein, prebiotics, probiotics, nucleotides and beta-carotene, fed to infants within the first months of life.MethodsThis was a non-randomized, open, uncontrolled study conducted from December 2010 to May 2011. Twenty-three healthy infants aged 10 days to 2 months old were enrolled. Outcomes included gastrointestinal tolerance, physical growth and safety. Prior to the initiation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…There is very little information for healthcare providers to help guide mothers in their post-birth recovery or their nutritional transition to motherhood. Multiple studies have supplemented infants with lutein and zeaxanthin, demonstrating these nutrients are safe and effective in increasing plasma concentrations of lutein and zeaxanthin and reducing oxidative stress and inflammation [260][261][262][263][264][265][266]. Plasma lutein levels in infants have been shown to correlate with the saturated response amplitude in rod photoreceptors, suggesting that lutein helps protect photoreceptors and potentially impacts retinal development through its ability to reduce inflammation [266].…”
Section: Vitamin B12mentioning
confidence: 99%
“…There is very little information for healthcare providers to help guide mothers in their post-birth recovery or their nutritional transition to motherhood. Multiple studies have supplemented infants with lutein and zeaxanthin, demonstrating these nutrients are safe and effective in increasing plasma concentrations of lutein and zeaxanthin and reducing oxidative stress and inflammation [260][261][262][263][264][265][266]. Plasma lutein levels in infants have been shown to correlate with the saturated response amplitude in rod photoreceptors, suggesting that lutein helps protect photoreceptors and potentially impacts retinal development through its ability to reduce inflammation [266].…”
Section: Vitamin B12mentioning
confidence: 99%
“…The French cheese named vieux-pan contains the carotenoid produced by Brevibacterium linens due to its orange-red-brown color that improves the sensory quality of the product [70]. In Russia, infant formulas are enriched with natural pigments such as lutein, which is present in breast milk, in order to improve children's health [71].…”
Section: Importance and Use Of Carotenoids In Food Productsmentioning
confidence: 99%
“…60 It functions as a structural component of the eye, an antioxidant, and as a filter for blue light. Lutein plays a biological and physiological role in the visual development and function in infants; 61 and infants are reliant on breastfeeding to receive adequate quantities. 62 Differences in serum lutein content between breastfed and formula-fed infants are seen as early as 1 month of age.…”
Section: Luteinmentioning
confidence: 99%
“…63 Recent studies demonstrated that lutein-supplemented infant formula is safe and supports the visual and cognitive development of infants. [60][61][62]64 Presently, there is no research that lutein supplementation influences brain accretion during infancy. A recent study found that the concentration of lutein is higher in several regions of the brain during infancy than in adulthood which may indicate that lutein may play an important role in early neural development.…”
Section: Luteinmentioning
confidence: 99%
See 1 more Smart Citation